Current Views on Dopaminergic Drugs Affecting Glucose Homeostasis - Hassanabad, Mortaza F.; Fatehi, Mohammad (Current Diabetes Reviews, 2019)
Background: For more than three decades, it has been known that manipulation of dopaminergic system could affect glucose homesotasis in experimental animals. The notion that glucose homeostasis in human might be influenced by dopaminergic drugs has attracted a great deal of attention in the past two decades. In spite of rapid advancements in revealing involvement of dopaminergic neurotransmission in insulin release, glucose up-take and pancreatic beta cell function in general through centrally and peripherally controlled mechanisms, there are discrepancies among observations on experimental animals and human subjects. Conclusion: With the expansion of pharmacotherapy in psychotic conditions, depression and endocrine abnormalities along with a sharp increase in prevalence of type two diabetes and disturbances of glucose homeostasis as a major risk factor for many cardiovascular complications and associated mortalities; it seems a critical analysis of recent investigations on drugs which act as agonists or antagonists of dopaminergic receptors in various tissues and organs may provide better insight into how safe and efficient these medicines could be prescribed. Furthermore, the other main objective of present review is to compare clinical data on significance of changes in blood glucose and insulin levels during short term and after long term treatment with these agents. This in turn would be beneficial for determining adequate strategies to combat or to avoid adverse effects associated with dopaminergic drug therapy.
Keywords: Dopamine receptor